STRUCTURAL AND SEMANTIC CONCEPT OF “TERMIOSYSTEM” (Western European Journal of Medicine and Medical Science, 2024)
A targeted search using the information at hand can be used to describe the creation and construction of a words. Every time a new national or international language is developed, it is encoded, saved, and used. Languages require terminological information, of course. In linguistics, terminology has long been a significant topic. Because it is possible to understand the substance of an idea by defining the location and function of terms within the field's lexical levels. The adoption of a functional approach's guiding principles is also necessary for a thorough and in-depth analysis of the term's meaning